Effect of freeze-dried Carica papaya leaf juice on inflammatory cytokines production during dengue virus infection in AG129 mice - Nor Azrina Norahmad; Mohd Ridzuan Mohd Abd Razak; Norazlan Mohmad Misnan; Nur Hana Md Jelas; Umi Rubiah Sastu; Amirrudin Muhammad; Tiffiny Chau Dee Ho; Bazilah Jusoh; Nor Azlina Zolkifli; Ravindran Thayan; Adiratna Mat Ripen; Murizal Zainol; et al. (BMC, 2019)
Abstract Background Carica papaya leaves have been used for traditional treatment of dengue fever and have been reported to exhibit an immunomodulatory activity by affecting the level of cytokine production in vitro and in vivo. Due to the lack of adequate in vivo evidence in dengue disease model, the present study was initiated to screen and identify the cytokines affected by freeze-dried C. papaya leaf juice (FCPLJ) treatment in AG129 mice infected with DEN-2 dengue virus. Methods The AG129 mice were fed orally with FCPLJ for 3 consecutive days after 24 h of dengue virus inoculation. Plasma cytokines were screened by using ProcartaPlex immunoassay. The gene expression in the liver was analyzed by using RT2 Profiler PCR Array. Results The results showed that FCPLJ treatment has increased the plasma CCL2/MCP-1 level during peak of viremia. Gene expression study has identified 8 inflammatory cytokine genes which were downregulated in the liver of infected AG129 mice treated with FCPLJ. The downregulated inflammatory cytokine genes were CCL6/MRP-1, CCL8/MCP-2, CCL12/MCP-5, CCL17/TARC, IL1R1, IL1RN/IL1Ra, NAMPT/PBEF1 and PF4/CXCL4. Conclusion The findings indicated the possible immunomodulatory role of FCPLJ during dengue virus infection in AG129 mice.